ANALYSIS OF WORK DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE AT PT ESS JAY STUDIOS, WEST JAKARTA - Muhamad Abid; Noto Susanto; Widowati Widowati (International Journal Management and Economic, 2025)
This study aims to analyze the relationship between work discipline and employee performance at PT ESS JAY Studios, West Jakarta. The research uses a qualitative approach, with data collected through interviews, direct observation, and documentation from a sample of 26 employees. Work discipline encompasses dimensions of time, adherence to rules, and responsibility, while employee performance is measured based on work quality, productivity, and initiative in completing tasks. The results show that work discipline significantly impacts employee performance. The implementation of good time discipline enhances work efficiency and productivity, while adherence to rules creates a conducive work environment. A high level of responsibility encourages employees to complete tasks effectively without additional guidance. Although most employees demonstrate good performance, challenges remain, such as a lack of initiative and difficulties in teamwork. The study concludes that consistent application of work discipline can significantly improve employee performance. PT ESS JAY Studios is advised to strengthen its work discipline policies, provide relevant training, and create a supportive work environment to enhance productivity and the quality of production outcomes.